Using an Existential Psychotherapy Framework to Assist Students in Mindful Internet Use. Issue 1 (2nd January 2016) - Eells, Gregory T.
ABSTRACT: The use of the mobile Internet continues to play an increasing role in all of our lives and particularly in the lives of college and university students. Questions have been raised about the impact of the Internet on adolescents' and college students' fulfillment of traditional developmental tasks and more broadly their mental health. The present article posits potentially negative values associated with Internet use and shows how existential psychotherapy promotes corrective values that can help students navigate their Internet use. The existential psychotherapy framework brings mindfulness and conscious choice into students' decision-making process. This approach intentionally focuses on universal aspects of being human such as dealing with death, making decisions, confronting isolation, and creating meaning. The article will conclude with a case vignette on applying an existential psychotherapy framework to working with a college student.